2011
DOI: 10.1001/archoto.2011.114
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Sphincter Pharyngoplasty and Palatal Lengthening for Velopharyngeal Insufficiency<subtitle>A 10-Year Experience</subtitle>

Abstract: Sphincter pharyngoplasty is an effective procedure for the management of VPI, with a success rate of 87% when using need for surgical revision as the primary outcome measure. This number improved to 100% after a single revision, with elimination of VPI in all revision cases. Concomitant FP and SP may improve outcomes compared with SP alone. Further prospective studies are needed to elucidate this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
(48 reference statements)
1
34
1
Order By: Relevance
“…11 The combined procedure addresses the potentially multifactorial pathophysiology of velopharyngeal insufficiency with velar musculature repositioning, soft palatal lengthening, lateral pharyngeal constriction, and an overall decrease in velopharyngeal gap size. Restoring all of these physiologic components of the velopharyngeal sphincter mechanism might theoretically result in improved speech outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11 The combined procedure addresses the potentially multifactorial pathophysiology of velopharyngeal insufficiency with velar musculature repositioning, soft palatal lengthening, lateral pharyngeal constriction, and an overall decrease in velopharyngeal gap size. Restoring all of these physiologic components of the velopharyngeal sphincter mechanism might theoretically result in improved speech outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…19-21 Riski et al 22 observed the primary cause of failed pharyngoplasty was insertion of the flap below the point of optimal velopharyngeal closure. Studies have emphasized the importance of placement of the pharyngoplasty as it relates to speech outcome 20,23,24 , suggesting placement at or above the level of velopharyngeal closure 20,22,24 . However, clinical methods tend to be less prescriptive indicating placement should be “as high as possible.” The first cervical vertebra (C1) or the level of velopharyngeal closure have been recommended as landmarks for identifying placement of the pharyngoplasty prior to and during surgery in order to ensure the pharyngoplasty is at an optimal level for normal resonance postsurgically.…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 4 The aim of this study was to assess the efficacy of performing Furlow double opposing Z-plasty for patients presented with post-palatoplasty VPI.…”
Section: Page 4 Of 14mentioning
confidence: 99%
“…It can be used as a single procedure for treatment of VPI, and may be combined with another method as sphincter pharyngoplasty in severe cases[4, 22].…”
mentioning
confidence: 99%